2022
DOI: 10.1088/1361-648x/ac43fe
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of TaAs2 topological semimetal investigated by transport and ARPES

Abstract: We have performed electron transport and ARPES measurements on single crystals of transition metal dipnictide TaA$s_{2}$ cleaved along the ($\overline{2}$ 0 1) surface which has the lowest cleavage energy. A Fourier transform of the Shubnikov-de Haas oscillations shows four different peaks whose angular dependence was studied with respect to the angle between magnetic field and the [$\overline{2}$ 0 1] direction. The results indicate elliptical shape of the Fermi surface cross-sections. Additionally, a mobilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Result of Laue diffraction to identify the orientation of the cleaved surface is presented in figure 2 and results of the ARPES measurements are presented in figures 3 and 4 to reveal the detailed electronic structure of TaAs 2 . The experimental Laue diffraction pattern is seen to match well with the QLaue simulation for the (201) plane, indicating that the favorable cleaving surface of TaAs 2 is the (201) surface, which also has the lowest cleavage energy [58]. This surface is different from the (010) surface that is predicted to host rotational crystalline-symmetry-protected surface states [17].…”
Section: Resultsmentioning
confidence: 58%
“…Result of Laue diffraction to identify the orientation of the cleaved surface is presented in figure 2 and results of the ARPES measurements are presented in figures 3 and 4 to reveal the detailed electronic structure of TaAs 2 . The experimental Laue diffraction pattern is seen to match well with the QLaue simulation for the (201) plane, indicating that the favorable cleaving surface of TaAs 2 is the (201) surface, which also has the lowest cleavage energy [58]. This surface is different from the (010) surface that is predicted to host rotational crystalline-symmetry-protected surface states [17].…”
Section: Resultsmentioning
confidence: 58%
“…In the Γ 7 5 and Γ 7 6 levels, for k x ≲ 0.02 Å the linear RSO interaction strength is one order magnitude higher than the cubic type RSO with α R1 = 43 meVÅ and α R1 = 260 meVÅ. It is worthy to mention that in a recent study on TaAs 2 semimetal, the maximum spin splitting in Ta has been found to be 269 meV [52]. In this article, we have found that a larger splitting in Ta can be achieved by using oxide heterostructure of Ta-based material.…”
Section: Type-i Heterostructure Without Socmentioning
confidence: 56%
“…The values of the Hubbard parameter used for the d-orbitals of V are U = 4 eV for VSi 2 P 4 , and 2 eV for VSi 2 As 4 and VSiGeP 2 As 2 , and the Hund coupling J H is set at 0.87 eV. The main source of SOC in this compound is As; the value of SOC for As is estimated to be 0.164 eV [ 68 , 69 ].…”
Section: Computational Detailsmentioning
confidence: 99%